Role of sources and temporal sinks in a marine amphipod - Munguia, Pablo (Biol Lett, 2015)
Spatially structured habitats challenge populations to have positive growth rates and species often rely on dispersing propagules to occupy habitats outside their fundamental niche. Most marine species show two main life stages, a dispersing stage and a sedentary stage affecting distribution and abundance patterns. An experimental study on Corophium acherusicum, a colonial tube-building amphipod, showed the strong influence that a source population can have on new habitats. More importantly, this study shows the effect of temporal sinks where newly established populations can show reduced growth rates if the propagule supply from a source is removed. Sink populations had a reduction in abundance and became male-biased as females left colonies. The consequences arising from short-term dispersal and temporal sinks could be due to different selection pressures at the source and sink populations. These consequences can become reflected in long-term dynamics of marine populations if we shift focus to non-random dispersal models incorporating behaviour and stage-dependent dispersal.